Method of extraction and characterization of oligosaccarides from palm kernel cake - Liang, Juan Boo (2012)

(untitled)
A method for producing multiple oligosaccharides having a potential prebiotic effect from a palm kernel cake includes the steps of providing the palm kernel cake into a solvent, extracting and separating the multiple oligosaccharides from the palm kernel cake, quantifying the multiple oligosaccharides by using at least one chromatography method and characterizing the multiple oligosaccharides. The multiple oligosaccharides act as a prebiotic and substrate for at least one strain of lactic acid bacteria.